What is the appropriate role of the trial statistician in preparing and presenting interim findings to an independent Data Monitoring Committee in the U.S. Cancer Cooperative Group setting? - Bryant, John (Statistics in medicine, 2004)
A recent draft FDA Guidance on the establishment and operation of clinical trial Data Monitoring Committees (DMCs) suggests that statisticians who prepare and present interim analyses to the DMC should be external to the trial sponsor. In the context of the National Cancer Institute (NCI) Cooperative Group program, this recommendation appears to imply that Group study statisticians should be blinded to interim data and excluded from the interim monitoring process in all Cooperative Group trials. In this commentary, it is argued that the benefits of such a policy would be minimal in the Cooperative Group setting and are far outweighed by the tangible benefits of including the study statistician in the monitoring process. Copyright 2004 John Wiley & Sons, Ltd.